INFLUENCE OF E-LEARNING SERVICE QUALITY ON E-LEARNING STUDENT LOYALTY THROUGH E-LEARNING STUDENT SATISFACTION AT UNIVERSITY IN EAST JAVA - Sarah Rosa Dayanti; Romi Ilham (Jurnal Bisnis dan Keuangan, 2022)
More than one year has passed since the Covid-19 pandemic in Indonesia, which has impacted the distance learning process. E-learning is one of the facilities provided by the University that helps the course of online lectures. This study aims to determine the effect of e-learning service quality on e-learning student loyalty through e-learning student satisfaction. The method used is a quantitative method with data collection, distributing questionnaires to active users of e-learning at universities in East Java. The data were analyzed using WarpPLS 7.0. The results in this study indicate that e-learning service quality affects e-learning student satisfaction and e-learning student loyalty. Likewise, e-learning student satisfaction affects e-learning student loyalty.